ADVANCEMENTS IN SURGICAL TECHNIQUES: A COMPREHENSIVE REVIEW - Kholmamatova Shahzoda; Imran Aslam; Ayesha Ashraf; Abdurakhmanova Zamira Ergashboevna; Eshkobilova Mavjuda Ergashboevna (TADQIQOTLAR, 2025)
Abstract: Surgery has been an essential component of medical practice for many years, continuously improving patient outcomes and reducing morbidity and death. This  research  article  provides  an  overview  of  recent  advancements  in  surgical techniques  from  a  range  of  disciplines.  It  examines  developments  in  minimally invasive surgery, tissue engineering, artificial intelligence (AI), robotic surgery, and augmented reality (AR). It also discusses the challenges that the surgical profession will face in the future, including the importance of surgeon education and training and the ethical implications of new technological developments.